Wheat stripe rust detection of probable alarm zones in Rabi 2012-13 and 2013-14 seasons - Dutta, Sujay; Saharan, Mahender Singh; Sharma, Indu (Journal of Cereal Research, 2016)
In India, earliest reviews pointed that awareness of the role of weather on pests and diseases existed in the early forties. Mehta (1940) pioneered the work on the role of environmental factors in the epidemiology of wheat rust. Wheat rusts are weather sensitive and determining weather conditions conducive for their growth and their proliferation can help in locating the likely regions and periods of occurrence. Short and medium-range weather forecasts make models as useful planning tools for initiation of control measures on the basis of weather warnings. Monitoring one or more important weather parameters for initiation of a pest and disease would merit the issue of a warning in the form of likely pest alarm zones. Aim of this study was to identify stripe rust (yellow rust) affected areas of wheat crop using combination of weather data and satellite remote sensing data.